Partisipasi Masyarakat dalam Pelaksanaan Program Kampung Iklim (Proklim) di Desa Gribig Kecamatan Gebog Kabupaten Kudus - Handayani, Lilis; Wiranti, Dwiana Asih; Anissatussa’diyah, Anissatussa’diyah; Layalya, Laili Alya; Haikalinnur, Muhammad (Journal of Dedicators Community, 2024)
Increasing the quality of teachers in preparing literacy and numeracy questions through technical guidance activities on numeracy literacy so that they are able to support the implementation of the curriculum according to the standards set by the government.  Changes in the curriculum in Indonesia encourage teachers to always be able to develop their abilities in terms of preparing valid questions so that it has an impact on the appropriateness of the assessments prepared by teachers. The government's socialization is still uneven due to the pandemic, so the team has mobilized to serve UIN Maulana Malik Ibrahim Malang to participate in socializing the material at MIS Almaarif 09 Randuagung Singosari and MI Ar Raudhah Lawang.The method used is Participatory Action Research (PAR). The theory used in this service, namely Maslow's theory, results in an increase in teacher quality, especially the ability to understand numeracy literacy material and develop valid numeracy literacy questions.Technical guidance activities are carried out in 4 stages, namely observation, providing material, then practical activities and evaluation.The resulting teacher response was 31.3%, the result was strongly agree, which showed a positive response, then 62% of them responded in agreement, so the percentage certainly shows the success of the implementation of technical guidance which can be seen from the way the teacher prepares numeracy literacy questions in accordance with the characteristics standardized by the government in the new curriculumAbstrakMeningkatnya kualitas guru dalam penyusunan soal literasi dan numerasi melalui kegiatan bimbingan teknis literasi numerasi sehingga mampu menunjang keterlaksanan kurikulum sesuai standar yang ditetapkan oleh pemerintah. Perubahan kurikulum di Indonesia mendorong guru untuk selalu bisa mengembangkan kemampuannya dalam hal penyusunan soal yang valid sehingga berdampak pada sesuainya asesmen yang disusun guru. Sosialisasi pemerintah masih belum merata karena pandemi sehingga menggerakkan tim mengabdi UIN Maulana Malik Ibrahim Malang ikut serta dalam mensosialisasikan materi tersebut di MIS Almaarif 09 Randuagung Singosari dan MI Ar Raudhah Lawang. Metode yang digunakan yaitu Participatory Action Research (PAR). Teori yang digunakan dalam pengabdian ini yaitu teori Maslow menghasilkan peningkatan kualitas guru khususnya kemampuan dalam pemahaman materi literasi numerasi dan pengembangan penyusunan soal literasi numerasi yang valid. Kegiatan bimbingan teknik terlaksana selama 4 kali tahapan yaitu observasi, pemberian materi kemudian kegiatan praktik dan evaluasi. Respon guru yang dihasilkan sebesar 31.3% di peroleh hasil sangat setuju yang menunujukkan respon positif kemudian 62 % mereka merespon setuju sehingga prosesntase tentunya menunjukkan keberhasilan terlaksakannya bimbingan teknik yang dapat dilihat dari cara guru dalam menyusun soal literasi numerasi sesuai dengan karakteristik yang distandarkan oleh pemerintah dikurikulum yang terbaru.Key word: Technical guidance, Protoype, Teacher, Madrasah Ibtidaiyah AbstractIncreasing the quality of teachers in preparing literacy and numeracy questions through technical guidance activities on numeracy literacy so that they are able to support the implementation of the curriculum according to the standards set by the government.  Changes in the curriculum in Indonesia encourage teachers to always be able to develop their abilities in terms of preparing valid questions so that it has an impact on the appropriateness of the assessments prepared by teachers. The government's socialization is still uneven due to the pandemic, so the team has mobilized to serve UIN Maulana Malik Ibrahim Malang to participate in socializing the material at MIS Almaarif 09 Randuagung Singosari and MI Ar Raudhah Lawang.The method used is Participatory Action Research (PAR). The theory used in this service, namely Maslow's theory, results in an increase in teacher quality, especially the ability to understand numeracy literacy material and develop valid numeracy literacy questions.Technical guidance activities are carried out in 4 stages, namely observation, providing material, then practical activities and evaluation.The resulting teacher response was 31.3%, the result was strongly agree, which showed a positive response, then 62% of them responded in agreement, so the percentage certainly shows the success of the implementation of technical guidance which can be seen from the way the teacher prepares numeracy literacy questions in accordance with the characteristics standardized by the government in the new curriculum. Kata KunciBimbingan teknik, Prototipe, Guru, Madrasah Ibtidaiyah AbstrakMeningkatnya kualitas guru dalam penyusunan soal literasi dan numerasi melalui kegiatan bimbingan teknis literasi numerasi sehingga mampu menunjang keterlaksanan kurikulum sesuai standar yang ditetapkan oleh pemerintah. Perubahan kurikulum di Indonesia mendorong guru untuk selalu bisa mengembangkan kemampuannya dalam hal penyusunan soal yang valid sehingga berdampak pada sesuainya asesmen yang disusun guru. Sosialisasi pemerintah masih belum merata karena pandemi sehingga menggerakkan tim mengabdi UIN Maulana Malik Ibrahim Malang ikut serta dalam mensosialisasikan materi tersebut di MIS Almaarif 09 Randuagung Singosari dan MI Ar Raudhah Lawang. Metode yang digunakan yaitu Participatory Action Research (PAR). Teori yang digunakan dalam pengabdian ini yaitu teori Maslow menghasilkan peningkatan kualitas guru khususnya kemampuan dalam pemahaman materi literasi numerasi dan pengembangan penyusunan soal literasi numerasi yang valid. Kegiatan bimbingan teknik terlaksana selama 4 kali tahapan yaitu observasi, pemberian materi kemudian kegiatan praktik dan evaluasi. Respon guru yang dihasilkan sebesar 31.3% di peroleh hasil sangat setuju yang menunujukkan respon positif kemudian 62 % mereka merespon setuju sehingga prosesntase tentunya menunjukkan keberhasilan terlaksakannya bimbingan teknik yang dapat dilihat dari cara guru dalam menyusun soal literasi numerasi sesuai dengan karakteristik yang distandarkan oleh pemerintah dikurikulum yang terbaru